Return to Collegiate Hockey After Repair of Chronic Biceps Femoris Tendon Transection at the Knee: A Case Report. Issue 3 (July 2019) - Day, Molly A.; Owens, Jessell M.; Rosneck, James T.; Westermann, Robert W.
Abstract : Case: A 22-year-old man sustained complete transection of his right distal biceps femoris tendon by a hockey skate. He experienced persistent pain and disability, symptoms of peroneal neuritis, and an inability to return to hockey. At 3-months postinjury, he underwent biceps femoris repair and peroneal neurolysis. At 9-months postoperatively, the patient returned to full activity and played a full season collegiate hockey. Conclusions: Isolated distal biceps femoris transection is rare and may be associated with peroneal neuritis. Primary repair and peroneal neurolysis is a viable treatment option (even 3 months postinjury), with satisfactory outcomes and full return to high-level activity.